2016
DOI: 10.15376/biores.12.1.533-545
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardant Efficiency of Melamine Pyrophosphate with Added Mg-Al-Layered Double Hydroxide in Medium Density Fiberboards

Abstract: The main objective of this study was to investigate the flame retardant (FR) efficiency of melamine pyrophosphate (MP) with added layered double hydroxide (LDH) in medium density fiberboards (MDFs) to be used as building decorative materials. The thermal degradation, FR efficiency, and combustion properties of MDF were analyzed by Fourier transform infrared spectra (FTIR), thermogravimetric analysis (TGA), limiting oxygen index (LOI) test, and cone calorimetric test. The TGA results showed that the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The effect of the concentration of the combustible gas produced by the solution makes the combustion proceed slowly and achieves the flame retardant effect. The gas phase flame retardancy of composite flame retardants is the result of the combined action of "cooling effect" and "dilution effect" [53]. Hence, the synergistic action between TM LDHs and DTPMP can effectively inhibit smoke and heat release and improve the fire safety of EP.…”
Section: Flame Retardant Mechanism Analysismentioning
confidence: 99%
“…The effect of the concentration of the combustible gas produced by the solution makes the combustion proceed slowly and achieves the flame retardant effect. The gas phase flame retardancy of composite flame retardants is the result of the combined action of "cooling effect" and "dilution effect" [53]. Hence, the synergistic action between TM LDHs and DTPMP can effectively inhibit smoke and heat release and improve the fire safety of EP.…”
Section: Flame Retardant Mechanism Analysismentioning
confidence: 99%
“…A cone calorimeter (Fire Testing Technology, East Grinstead, UK) and FT-IR (Midac Co., MA, USA) were used for the analysis of calorific value and combustion gas. The cone calorimeter is widely used to measure the calorific value of samples (Seo et al 2016;Liang et al 2017), and FT-IR is mainly used to look at the chemical bonding of solids (Cal et al 2016;Li et al 2017), but in this study, it was used for a combustion gas analysis. Calorific value measurement was conducted in accordance with ISO 5660-1 (2015), and the combustion gas analysis was conducted in accordance with the test method specified in ISO 19702 (2015).…”
Section: Analysis Of Calorific Value and Combustion Gas Of Wood Flourmentioning
confidence: 99%
“…Guo et al applied MgAl-LDH to wood in a two-step process and found that the total smoke production and maximum smoke production ratio were reduced by 58% and 41%, respectively, compared to those of samples without MgAl-LDH [12]. Liang et al introduced 5.0 wt% MgAl-LDH and 5.0 wt% melamine pyrophosphate to medium density fiberboards and found that the peak heat release rate (PHRR) and mean heat release rate (MHRR) were reduced by 27.9% and 7.5%, respectively, compared to those of samples with 3.3 wt% MgAl-LDH and 6.7 wt% melamine pyrophosphate [13]. Wang et al reported the synthesis of ZnAl-LDH coating on the surface of wood to enhance the fire resistance of wood [14].…”
Section: Introductionmentioning
confidence: 99%